Dietary rosemary oil with/without zymogen forte improves water quality, growth hormones, immune-physiological response, stress resilience, and health status of Chelon ramada grown in groundwater - Ashraf I. G. Elhetawy; Mohammed F. El Basuini; Ahmed I. A. Mansour; Shimaa A. Shahin; Amira A. Omar; Mohamed M. Zayed; Mohamed M. Abdel-Rahim (BMC Veterinary Research)
Abstract With freshwater resources becoming scarce worldwide, mariculture is a promising avenue to sustain aquaculture development, especially by incorporating brackish and saline groundwater (GW) use into fish farming. A 75-day rearing trial was conducted to evaluate fish growth, immune response, overall health, and water quality of Chelon ramada cultured in brackish GW and fed on a basal diet (BD) augmented with rosemary oil (RO) or RO + zymogen forte™ (ZF) as an anti-flatulent. Five treatments were administrated in triplicate: T1: fish-fed BD without additives (control group); T2: fish-fed BD + 0.5 g RO /kg diet; T3: fish-fed BD + 0.5 g RO and 1 g ZF /kg diet; T4: fish-fed BD + 1 g RO /kg diet; T5: fish-fed BD + 1 g RO and 1 g ZF /kg diet. Three hundred fish (8.51 ± 0.01 g/fish) were housed in 15 fiberglass tanks (1500-L tank). The results revealed significant improvements (P < 0.05) in growth performance, survival, growth hormone, and insulin-like growth factor-1. Additionally, there were decreases in the feed conversion ratio (FCR) and the levels of nitrogen by-products (NH4, NH3, and NO2) and pathogenic bacterial counts in the rearing water when fish were fed diets supplemented with RO and RO + ZF. Furthermore, significant reductions in the levels of plasma stress indicators (cortisol, creatinine, and glucose) were detected. In addition, there were significant enhancements observed in the levels of innate immune markers, such as white blood cells, total protein, albumin, and immunoglobulin. The complement system, specifically complement 3 and complement 4, also showed considerable improvements. Furthermore, there were increases in plasma heat shock proteins HSP70 and HSP90, as well as enhanced antioxidant activity. These gains were associated with healthier liver and intestines. The investigation demonstrated that adding 0.5–1 g RO / kg diet or RO + ZF to a C. ramada diet has many benefits, including reducing the levels of nitrogen by-product chemicals and pathogenic bacterial load in GW used in growth tanks. Furthermore, significant improvements were observed in the rates of growth and associated hormones, efficiency of feed utilization, blood indicators, immune function, condition of internal organs (namely the intestine and liver), and overall health of the fish.